2011
DOI: 10.1212/wnl.0b013e31823648a6
|View full text |Cite
|
Sign up to set email alerts
|

Early seizures in intracerebral hemorrhage

Abstract: ES are a frequent complication in patients with spontaneous ICH; however, their occurrence does not influence outcome at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
143
5
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 38 publications
7
143
5
6
Order By: Relevance
“…Convulsive seizures may become less frequent, and clinical seizure manifestations may be more difficult to recognize in the elderly. 25 Several previous studies, 3,4,19,20,24,26 in line with our results, reported that cortical and lobar ICH represent highly epileptogenic lesions. Electrophysiological studies showed greater probability of spontaneous synaptic events and increased excitability in response to synaptic stimulation in neurons adjacent to cortical lesion compared with those surrounding glia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Convulsive seizures may become less frequent, and clinical seizure manifestations may be more difficult to recognize in the elderly. 25 Several previous studies, 3,4,19,20,24,26 in line with our results, reported that cortical and lobar ICH represent highly epileptogenic lesions. Electrophysiological studies showed greater probability of spontaneous synaptic events and increased excitability in response to synaptic stimulation in neurons adjacent to cortical lesion compared with those surrounding glia.…”
Section: Discussionsupporting
confidence: 92%
“…Cumulative risk of LS was 7.1% at 1 year after ICH and 11.8% at 5 years. This is in line with earlier reports [3][4][5]19,20 although comparisons between studies are difficult because of different patient populations, seizure criteria, and follow-up…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Literatüre göre inme sonrası akut semptomlu nöbetler ilk birinci haftada ortaya çıkar ve bu durum daha çok intraserebral hemorajilerde (%14) görülmektedir. [4] Geç nöbet insidansı ise %3-14 olup en sık üçüncü ay ya da birinci yılda epilepsi meydana gelmektedir. [5,6] Bu çalışmada akut semptomatik nöbet geçiren hastalar dahil edilmemiştir.…”
Section: Discussionunclassified